Clinical Profile and Prescribing Pattern of Cirrhosis in a Tertiary Care Hospital - Vijayan, Meenu; A, Anisha K; Selina, Arjun Sanal Kumar; R, Roshni P (Indian Journal of Pharmacy Practice)
Liver cirrhosis is one of the major non communicable diseases, which is expected to be a prime health care concern of the 21stcentury. In the present world, the number of persons suffering from the liver disorders is increasing. This may be due to the change in lifestyle and many stress related factors. Identification of the demography of patients with cirrhosis is of great importance in the current health care scenario for the calculation of prevalence of this frustrating disease. The aim of the study was to observe the clinical profile and treatment pattern in cirrhotic patients. This was an observational prospective study carried out in in-patient department of Gastroenterology, Amrita Institute of Medical Sciences for a period of 8 months. 150 patients diagnosed with liver cirrhosis and who satisfied the inclusion criteria were included. Specially designed standardized data collection form was used. From this study, we identified that the majority of the patients were male who belonged to the age group 51–60 years and majority of them were from urban area. Positive family history was noted in few patients. Abdominal pain was the most frequent symptom seen in majority of the cirrhotic patients. Most of the patients belonged to the Child Pugh Class C category. Antibiotics were the most commonly prescribed category of drug. Among this, cephalosporins were the most frequently used drug.
Keywords: Cirrhosis; Clinical profile; Prescribing Pattern; Demographics